Response of ornamental plant Aster to inoculation of various inoculant of soil microbial consortia - Hindersah, Reginawanti; Fitriatin, Betty Natalie; Setiawati, Mieke Rochimi; Suryatmana, Pujawati; Aditya, Fasa; Nugraha, Gita Bina (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2024)
The Aster (Callistephus chinensis L) is an important commodity and is cultivated by using NPK fertilizer. The other nutrient source in environmental-friendly agriculture is biofertilizer contains mixed strains of beneficial microbes. The purpose of a field experiment was to observe the influence of various biofertilizer composed of mixed strain of Nitrogen-fixer bacteria and Phosphate-solubilizer microbes on Aster plant growth and yield of flower. The research design was a randomized block design consisted of four biofertilizer types and one control. The results verified that biofertilizer increased plant height at 9 weeks after application but have not affected the initial generative stadia. The consortia of Pseudomonas diminuta, P. Cepaceae, Penicillium sp., and Aspergillus sp. showed the best effect on the plant health, flower number per plot, and flower diameter. The experiment confirmed that all biofertilizers could be used as the source of biostimulants for Aster.